2019
DOI: 10.33314/jnhrc.v17i01.1827
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infertility in Couples

Abstract: Background: Infertility is defined as a couple’s inability to conceive after a period of twelve months of regular unprotected intercourse. Infertility globally affects approximately 10-15% of couples. This study was carried out to find out the determinants of infertility among infertile couples.Methods: This is a retrospective review of records of 3231 infertile couples in the Department of Obstetrics and Gynecology, Dhulikhel Hospital from January 1, 2008 to June 30, 2018. A total of 3231 infertile couples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 0 publications
5
53
1
Order By: Relevance
“…3 We found the mean age at which couples seek treatment is 27.25 ± DOI: 10.3126/jpn.v10i2.27267 4.12 years, similar to reports from other researchers. 4,10 This mean age is also near to the documented global mean age of childbearing since 1970. 3 In the age below 20 years and above 45 years, fewer couples are seeking a child.…”
Section: Discussionmentioning
confidence: 63%
“…3 We found the mean age at which couples seek treatment is 27.25 ± DOI: 10.3126/jpn.v10i2.27267 4.12 years, similar to reports from other researchers. 4,10 This mean age is also near to the documented global mean age of childbearing since 1970. 3 In the age below 20 years and above 45 years, fewer couples are seeking a child.…”
Section: Discussionmentioning
confidence: 63%
“…A large study comprise of ten years told male factor identified in 23.9% and abnormality in semen analysis in 22.7% and sexual dysfunction in 1.2% only. 13 Similarly another study showed male infertility in 40% subfertile couples. 14 The study by KoboriY tells male factors infertility in 50% of couples.…”
Section: Discussionmentioning
confidence: 93%
“…It also guides to fertility and not a certain proof of fertility of an individual except in cases of azoospermia where cumulative conception rate is zero. 13 The study highlighted that male factor exclusively contribute about 32% to subfertility. In study conducted in Nigeria showed male factor in 52.38%.…”
Section: Discussionmentioning
confidence: 97%
“…Infertility affects about 10-15% of couples worldwide and has become an increasingly common health problem (Tamrakar and Bastakoti, 2019). In recent years, assisted reproductive technology (ART) has become an important treatment for many women suffering from infertility.…”
Section: Introductionmentioning
confidence: 99%